Copie ou éloge ? Les porcelaines monochromes en rouge de cuivre d’époque Kangxi (1661-1722) imitant les porcelaines du règne de Xuande (1425-1435) - Valentina Bruccoleri (Les Cahiers de Framespa)
Under the reign of emperor Kangxi (1661-1722), the Chinese imperial kilns resumed the production of copper-red monochrome porcelains, luxury objects appreciated by emperors, as well as extremely difficult to achieve. These pieces, which were produced from the 14th century onward, reached their highest level of quality under the reign of Ming emperor Xuande (1425-1435), then declined progressively, in quality and quantity, until their total disappearance at the end of the 15th century. If copper-red porcelains of Kangxi’s reign look like copies of pieces of the Xuande period, a new parallel production of these monochromes developed, with innovative forms and nuances.